Predictors of Cyberbullying among Malaysian Youth - Akmar Hayati, Ahmad Ghazali; Asnarulkhadi, Abu Samah; Siti Zobaidah, Omar; Haslinda, Abdullah; Aminah, Ahmad; Hayrol Azril, Mohamed Shaffril (UNIMAS Publisher, 2020)
Cyberbullying has emerged of late as a serious issue, especially among the most active internet users in Malaysia – youths. As the number of related studies is still lacking, the present study aims to determine the predictors of cyberbullying among youths in Malaysia. The study is quantitative in nature and in total had involved 400 youths aged between 18 to 40 years old. The findings suggest that predictors such as age, loneliness, self-esteem, and empathy yielded significant relationship with cyberbullying, while males were predominantly reported to perpetrate cyberbullying than females. Several recommendations were highlighted and hopefully, it can assist any concerned parties in developing concrete strategies to reduce cyberbullying cases among youths in Malaysia further.